Exploring the link between teaching variables and Ghanaian junior high school mathematics achievement: The mediating role of teachers’ self – efficacy - Akosah, Ernest Frimpong; Yarhands Dissou, Arthur; Adu Obeng, Benjamin (American Journal of STEM Education, 2024)
This study investigates the mediating role of teachers' self-efficacy in the relationship between teacher knowledge, teaching quality, teaching experience, and students' mathematics achievement. Utilizing a quantitative research design, the study employs structural equation modeling (SEM) to analyze data collected from 507 junior high school mathematics teachers and their 5070 students across eight regions in Ghana. Participants were selected using a stratified purposive sampling technique. The data were analyzed using SPSS and AMOS version 23. The findings reveal that teacher knowledge significantly impacts students' mathematics achievement, while teaching quality and teaching experience also exhibit positive effects. Furthermore, teacher self-efficacy was found to partially mediate the relationships between teacher knowledge and mathematics achievement, as well as between teaching quality and mathematics achievement. These results highlight the critical role of teacher self-efficacy in enhancing mathematics education. The study underscores the importance of professional development programs that focus on improving teacher self-efficacy to boost students' performance in mathematics.